Lecture timetabling using heuristic technique - Emilia, Adzmi (2012)
The purpose of this paper is to try to develop a system about lecture timetabling problem.This project presents about Lecture Timetabling using Heuristic Method. Timetabling is a well known difficult combinatorial problem. In recent years,several techniques have been used to automatically generate university timetabling problems, including graph colouring heuristics and a lot more. Timetabling deals with the problem of placing certain resources into a limited number of time slots,subject to given constraints,in order to satisfy a set of stated objectives to the highest possible extent.In this paper,by using the proposed heuristic technique,a lecture timetable is produced considering some constraints that are able to be satisfied.Though it is impossible to consider all constraints in one timetable,the system proposed try to satisfied some of the constraints in order to generate the lecture timetable.